Taking Back the Workers' Law : How to Fight the Assault on Labor Rights - Dannin, Ellen (Cornell University Press, 2018)
Prolabor critics often question the effectiveness of the National Labor Relations Board. Some go so far as to call the Board labor's enemy number one. In a daring book that is sure to be controversial, Ellen Dannin argues that the blame actually lies with judicial decisions that have radically "rewritten" the National Labor Relations Act. But rather than simply bemoan this problem, Dannin offers concrete solutions for change. Dannin calls for labor to borrow from the strategy mapped out by the NAACP Legal Defense Fund in the early 1930s to eradicate legalized racial discrimination. This book lays out a long-term litigation strategy designed to overturn the cases that have undermined the NLRA and frustrated its policies. As with the NAACP, this strategy must take place in a context of activism to promote the NLRA policies of social and industrial democracy, solidarity, justice, and worker empowerment. Dannin contends that only by promoting these core purposes of the NLRA can unions survive-and even thrive.